Influence of values of angle of jet-joining on non-uniformity of water inflow along the path in pressure collector-pipeline - Cherniuk, Volodymyr; Ivaniv, Vasyl (International Conference “Environmental Engineering”, 2017)
Results of experimental investigation of the influence of values of the angle β at which jets join a pressure pipeline on the nonuniformity of water inflow along the collector-pipeline (CP) are presented. The inner diameter D of the CP is 11.28 mm, and the diameter d of the nozzles is 4.83 mm, d / D nozzles had been installed at angles β , the latter was given the values of: ο = 0 . 428 . Five CPs in which all the 0 ; ο 45 ; ο 90 ; ο 135 ; investiguated. A CP in which in the initial segment the nozzles had been installed at the angle ο 180 , where ο β 0 = , and in the middle and terminal segment β = 18 0 ο along the CP was obtained for CPs with has been also investigated. The greatest non-uniformity of the water inflow β = 9 0 ο , and the least one for CPs with diffrent values of the angle β . The obtained results give us the reason to conclude that it is possible to adjust the non-uniformity of water inflow into a CP by means of the method of selection of different values of angle β at which the jets join the CP.